Symposium 1: Networked Learning, a Relational Approach – Weak and Strong Ties - Jones, C.; Ferreday, D.; Hodgson, V. (Proceedings of the International Conference on Networked Learning, 2006)
In this paper, we explore the idea of weak ties in networked learning. We go back to the original conception of the strength of weak ties (Granovetter 1973) and relate this to a dialogic understanding of networked learning (Koschmann 1999, Dysthe 2002). These theoretical ideas are applied to the examination of two networked settings in which educational leaders exchange ideas and have the potential to create knowledge. We examine these networks from the point of view of the overall pattern of interaction and from an interest in the kinds of dialogues engaged in by participants in the network.